Quantitative Study of Human Scleral Melanocytes and Their Topographical Distribution. (1st December 2020) - Hu, Dan-Ning; Yao, Shen; Iacob, Codrin E.; Giovinazzo, Jerome; Rosen, Richard B.; Grossniklaus, Hans E.; Sassoon, Jodi
ABSTRACT: Purpose: While fibroblasts constitute the main cell component of the sclera, the purpose of the present study was to investigate the cell densities of melanocytes at different regions of the sclera, and to compare them with associated scleral fibroblast densities in human donor eye sections. Methods: . Paraffin-embedded sections of sclera from 21 human eyes were stained with hematoxylin-eosin (H&E) and immunohistochemical staining (S-100/AEC). Scleral melanocyte and fibroblast numbers were counted in different regions of the sclera. The relationship between the melanocyte density and iris pigmentation was also analyzed. Results: . Melanocytes were found in the posterior region of the sclera, especially around the vessels and nerves in emmissarial canals, whereas no or rare melanocytes were found in equatorial and anterior regions. In H&E sections, melanocyte densities in eyes with light-colored irides were significantly less than in eyes with medium or dark-colored irides ( P < .05). In S-100-stained sections, more melanocytes could be detected than those in the H&E sections in light-colored eyes ( P < .05), but not in medium or dark-colored eyes ( P > .05). The numbers of scleral fibroblasts were relatively stable in different regions. In the posterior scleral region, the numbers of fibroblasts were slightly higher than the number of melanocytes, however, this differences were not statistically significant ( P > .05). Conclusion: . Notable numbers of melanocytes were present in the posterior sclera suggesting that these cells may play a role in ocular physiology and in the pathogenesis of various disorders of the sclera.